The Impacts Of Hofstede’s Cultural Dimensions On International Trade Barriers - RA. afera ratna wijayanti; aswin andika putra; faizatul rizki (IULI Publisher, 2022)
Due to the advancement of communication and transportation technologies, the globaleconomy has never been more integrated. Hence, more businesses are trying to research andpenetrate new markets worldwide with superb marketing mixes. However, the one-size-fits- allapproach has proved to be ineffective; the endeavors are usually hampered by cultural differencesbetween countries reflected in the dimensions of the Hofstede Cultural Dimensions. The differences,especially in Power Distance, Long-term Orientation, and Indulgence, will play a crucial role inshaping the country’s international trade barriers, corporate culture, and eventually the preferredmarketing mix. Thus, attaining a comprehensive overview of a country’s culture is imperative for asuccessful business. Therefore, this paper tries to delve deeper and scrutinize the relationshipbetween the Hofstede Cultural Dimensions and international trade barriers.Keywords: culture, Hofstede Cultural Dimensions, international trade, international trade barriers